2022
DOI: 10.1155/2022/8342767
|View full text |Cite|
|
Sign up to set email alerts
|

An Automated Deep Learning Model for the Cerebellum Segmentation from Fetal Brain Images

Abstract: Cerebellum measures taken from routinely obtained ultrasound (US) images have been frequently employed to determine gestational age and identify developing central nervous system’s anatomical abnormalities. Standardized cerebellar assessments from large-scale clinical datasets are required to investigate correlations between the growing cerebellum and postnatal neurodevelopmental results. These studies could uncover structural abnormalities that could be employed as indicators to forecast neurodevelopmental an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…These challenges can be mitigated through the incorporation of techniques such as regularization parameter tuning and the strategic use of skip connections, as exemplified by ResNets. The inclusion of skip connections not only alleviates the vanishing gradient problem but also [58,[95][96][97][98][99][100][101][102][103]107,109,[115][116][117]120,[124][125][126][127][128][129][130][135][136][137]141,142,145,150,153,157,160,161,169]. Each study's color code reflects its relevance to a certain organ, including the heart, brain, lung, or analyzing for chromosomal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These challenges can be mitigated through the incorporation of techniques such as regularization parameter tuning and the strategic use of skip connections, as exemplified by ResNets. The inclusion of skip connections not only alleviates the vanishing gradient problem but also [58,[95][96][97][98][99][100][101][102][103]107,109,[115][116][117]120,[124][125][126][127][128][129][130][135][136][137]141,142,145,150,153,157,160,161,169]. Each study's color code reflects its relevance to a certain organ, including the heart, brain, lung, or analyzing for chromosomal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Each entry provides information about the employed methods, total number of images, key performance metrics, and application domain. [58,[95][96][97][98][99][100][101][102][103]107,109,[115][116][117]120,[124][125][126][127][128][129][130][135][136][137]141,142,145,150,153,157,160,161,169]. Each study's color code reflects its relevance to a certain organ, including the heart, brain, lung, or analyzing for chromosomal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, quantitative methods usually rely on automatic segmentation algorithms to achieve accurate and reproducible measurements. Deep convolutional neural networks have performed well in fetal medical image analysis, especially fetal brain segmentation [17].…”
Section: Advances In Mri Methodsmentioning
confidence: 99%
“…Researchers Xie et al [6,93] and Sahli et al [94] reported a method for classifying US images into a binary system of 'normal' and 'abnormal' cases, in which Xie et al additionally localized the structural lesions, which lead the algorithm to declare it 'abnormal' and thus recommend the clinician to recheck the labeled area. Lastly, the studies of Burgos-Artizzu et al and Sreelakshmy et al portrayed AI methods for the estimation of GA through an analysis of transthalamic axial planes or cerebellum measurements [95,96].…”
Section: Fetal Neurosonographymentioning
confidence: 99%